2017
DOI: 10.5539/elt.v10n12p72
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of L2 Experience and Vowel Context on the Perceptual Assimilation of English Fricatives by L2 Thai Learners

Abstract: The aim of this study is to investigate the effect of vowel context and language experience in the perceived similarity between L2 English fricatives and Thai sounds. The target English sounds being investigated were the sounds /v, f, w, θ, tʰ, s, ð, d, z, ʃ, t͡ ʃ/. These sounds were elicited from four native English speakers in words in onset position and followed by three vowel contexts: high, low and back. Subjects were 54 Thai students divided into two groups: English-major and non-English-major. These Tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Although some results are contrastive to the concept of the importance of the L2 experience in the L2 speech learning, many of them support this idea as shown in many previous studies (e.g., Kitikanan, 2017;Levy, 2009). For example, English /ae/ was mostly perceived as Thai /ae/ in the high-experienced group, but as Thai /a/ in the low-experienced group.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Although some results are contrastive to the concept of the importance of the L2 experience in the L2 speech learning, many of them support this idea as shown in many previous studies (e.g., Kitikanan, 2017;Levy, 2009). For example, English /ae/ was mostly perceived as Thai /ae/ in the high-experienced group, but as Thai /a/ in the low-experienced group.…”
Section: Discussionmentioning
confidence: 47%
“…The results showed that English diphthongs were consistently perceived as closer to Spanish diphthongs than to Spanish monophthongs. Although there are many studies on the perceived similarity between the English vowels and the L1 vowels, the number of perceptual assimilation research that includes the experience of the L2 (e.g., Kitikanan, 2017;Levy, 2009) is small despite the L2 experience has shown to be important in the L2 phonological learning. For example, in the study of Kitikanan (2017), the perceived similarity between English fricatives and related sounds, and L1 Thai categories was investigated.…”
Section: Rationale Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Richards (1969) and Kitikanan (2016) also suggested that /ʃ/ was difficult for L2 Thai learners to appropriately pronounce because of its nonexistence in their L1. /tʃ /and /ʃ/ were often substituted with the Thai affricate sound "ช" /tɕʰ/ in both production and perception by L2 Thai learners as they phonetically share the most features with /tɕʰ/ as supported in previous studies (Kitikanan, 2017;Richards, 1969). Briere and Chiachanpong (1980) even directly employed /tʃ/ to symbolize /tɕʰ/ or "ช" sound in the Thai stimuli of their study since they share the most similar place of articulation.…”
Section: Introductionsupporting
confidence: 52%
“…In the impressionistic analysis, /ʃ/ was deemed to have been articulated as [tʃ], like the word "shop" /ʃɒp/ realized as [tʃɒp], suggesting that /tʃ/ and /ʃ/ are problematic sounds for L2 Thai learners. Several research studies (Anam, 2018;Brière & Chiachanpono, 1980;Kitikanan, 2016Kitikanan, , 2017Pansottee, 1992;Richards, 1969;Roengpitya, 2011) have been put forward to address the production or perception of /tʃ/ and /ʃ/ sounds of L2 Thai learners. However, none of them have been conducted to explore the production of /tʃ/ and /ʃ/ sounds by L2 Thai learners by comparing them with the production of the Thai "ช" /tɕʰ/, and focusing on other factors such as vowel contexts and L2 learner's experience.…”
Section: Introductionmentioning
confidence: 99%